PSXI-18 Evaluation of Plasma Oxidation Products in Beef Calves Challenged with Lipopolysaccharide (LPS) Following Methionine Supplementation. (21st September 2022) - Barker, Sam N; Jackson, Treylr; Richeson, John T; Carroll, Jeff A; Burdick-Sanchez, Nicole C; Broadway, Paul Rand R; Legako, Jerrad F
Abstract: This study evaluated the plasma oxidative products of beef calves challenged with LPS following methionine supplementation (L0 = Control; L1 = 10 g/hd · d; L2 = 20 g/hd · d). Following an initial 40-d feeding period, steers (n = 32; 379kg±30.7) were challenged i.v. with LPS (0.25 µg/kg body weight) on d 41. Blood was collected at -2, 0, 2, 4, 6, 8, 10, 12, 18, 24, 36 and 48 h relative to the LPS challenge at 0 h. Samples were processed to isolate plasma for indicators of oxidative stress with colorimetric assays determining malondialdehyde (MDA) and reactive oxygen species (ROS) concentrations. Data were analyzed as repeated measures using the GLIMMIX procedure of SAS. Concentrations of MDA varied by time (P < 0.001), showing a large increase (P < 0.05) 2 h post-LPS, then decreasing again at 4 h. MDA values decreased (P < 0.05) from h 6 to 18 where values returned to initial concentrations (P < 0.05). A treatment × time interaction (P < 0.001) occurred for ROS concentrations. Concentrations for all treatments were less than the detectable limit at -2, 0, 10, 12, 24, 36, and 48h (P > 0.05). At 2 h post-LPS, ROS was greatest in L0 cattle, least in L2, and intermediate in L1 (P < 0.05), but declined at 4 h in all treatments. Values peaked at 6 h for L1 and L2 cattle, followed by a decline at 8 h (P < 0.05). Control cattle were similar from 4 to 6 h (P > 0.05) but increased again at 8 h (P < 0.05). These data show that oxidative stress from an LPS challenge contributes to increased plasma ROS and secondary lipid oxidation products but may be mitigated by the inclusion of methionine supplements.